Biological risk related to health care waste management in home care - Jéssica Fernanda Corrêa Cordeiro; Magda Fabbri Isaac Silva; Adriana Cristina de Oliveira; Silvia Rita Marin da Silva Canini (Universidade Federal do Ceará, 2019)
Objective: to describe the biological risk related to health care waste management in home care. Methods: this is a descriptive cross-sectional study that observed 231 home visits. The visits were made by 15 nursing professionals from a municipal home care service. Results: health care waste was generated during the home visits, being 49.5% of group A, 35.0% of group D and 15.5% of group E. Nonconformities were observed in the packaging of Group A and E waste. Group E waste was disposed of in rigid containers in 83.9% of the visits, but in 37.5%, it was disposed of in rigid containers suitable for this purpose. Conclusion: during home visits, group A, D and E health care waste was generated. The disposal and handling of group A and D waste showed that there was no packaging in appropriate plastic bags; in group E, the waste was discarded into a rigid container.